Protective effects of Ficus carica leaves on glucose and lipids levels, carbohydrate metabolism enzymes and β-cells in type 2 diabetic rats - Santiagu Stephen Irudayaraj; Sunil Christudas; Stalin Antony; Veeramuthu Duraipandiyan; Al-Dhabi Naif Abdullah; Savarimuthu Ignacimuthu (Taylor & Francis Group, 2017)
Context: The decoctions of Ficus carica Linn. (Moraceae) leaves are used in the folklore treatment of diabetes. Objective: To evaluate the effect of F. carica on glucose and lipids levels, carbohydrate metabolism enzymes and β-cells protective effects in type 2 diabetes. Material and methods: Diabetes was induced in 15 days high-fat diet (HFD)-fed Wistar rats by intraperitoneal injection of streptozotocin (STZ) (40 mg/kg). The ethyl acetate extract (250 and 500 mg/kg) of F. carica leaves was administered for 28 days. Oral glucose tolerance (OGTT) and intraperitoneal insulin tolerance tests (ITT) were evaluated on 15th and 25th days, respectively. Results: The ethyl acetate extract (250 and 500 mg/kg) of n F. carica leaves showed significant effect (p < 0.005) in the levels of blood glucose, total cholesterol (TC), triglycerides (TG), body weight and hepatic glycogen. In OGTT, F. carica (250 and 500 mg/kg) significantly (p < 0.005) detained the increase in blood glucose levels at 60 and 120 min and in ITT, F. carica enhanced the glucose utilization significantly (p < 0.005) over 30 and 60 min compared to diabetic control. Further, the altered activities of key carbohydrate metabolizing enzymes such as glucose-6-phosphatase, fructose-1,6-bisphosphatase and hexokinase in the liver tissue of diabetic rats were significantly (p < 0.005) reverted to near normal levels upon treatment with F. carica. Immumohistochemical studies of islets substantiated the cytoprotective effect on pancreatic β-cells. Discussion and conclusions: F. carica leaves exerted significant effect on carbohydrate metabolism enzymes with promising hypoglycemic and hypolipidemic activities in type 2 diabetic rats.